Estudo fitoquímico e avaliações da toxicidade aguda e atividades biológicas da raiz do vetiver (Vetiveria zizanioides L. Nash) Poaceae - BARROS, Gilvana Cristina de (2009)
The use of medicinal plants in controlling the diseases has shown its potential for the discovery of new medicines. Among the plant species used in the Hospital de Medicina Alternativa (HMA / SES-GO) highlights the vetiver (Vetiveria zizanioides L. Nash), an aromatic plant of the family Poaceae, used as a mild anti-hypertensive and diuretic. In this work it was investigated the chemical composition of the hydroalcoholic extract of vetiver, the freeze-dried aqueous extract and the essential oil from the roots of V. zizanioides. In the hydroalcoholic extract were found terpenoids compounds and / or saponins, flavonoids and phenolic acid. In the freeze-dried aqueous extract was observed the presence of flavonoids and phenols. In the essential oil 38 compounds were identified, and khusimol, palustrol, khusimona, zizanona and epi-α-vetivona were the major constituents. In the assessment of the acute toxicity of the hydroalcoholic extract and the freeze-dried aqueous extract of root of V. zizanioides, it was concluded that these extracts showed no toxicity at a dose of 2000 mg / kg. The freeze-dried aqueous extract of the roots of V. zizainoides showed no statistically significant diuretic action in the doses tested. In the investigation of antimicrobial activity, the essential oil of the root of V. zizanioides showed potent activity to inhibiting the growth of Staphylococcus aureus with MIC of 0.15 mg / mL. The crude ethanolic extract showed an antimicrobial activity with MIC of 0.19 mg / mL for Bacillus cereus and Micrococcus roseus and 0.39 mg / mL for Micrococcus luteus, S. aureus and Bacillus subtilis. The hexane fraction showed stronger antimicrobial activity against strains of M. luteus, M. roseus, S. aureus and B. cereus. This study could prove that the essential oil, the crude ethanol extract and hexane fraction from roots of V. zizanioides showed antimicrobial potential.